Iron mask [videorecording (DVD)] - Stepchenko, Oleg, 1964-; Cheng, Long, 1954-; Flemyng, Jason; Schwarzenegger, Arnold; Yao, Xingtong, 1983- (Lionsgate, 2020)
In order to save his homeland from certain doom, a kung fu master must escape from the maniacal James Hook in order to send his daughter a secret talisman that will allow her to control a massive and mythical dragon. This larger-than-life, globetrotting tale, ranges from the impenetrable Tower of London to the fabled Silk Road and China's Great Wall.